PENGARUH PROFESIONALISME, REWARD DAN PUNISHMENT TERHADAP KINERJA PERSONEL KEPOLISIAN RESOR BOLAANG MONGONDOW TIMUR - Tambajong, Geraldy; Irvan Trang; Tielung, Maria V. J. (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
Police performance refers to the extent to which the Indonesian National Police (Polri) has successfully carried out its main role, namely maintaining public security and order, enforcing the law, and providing protection, guidance, and services to the community. The purpose of this study is to determine the influence of Professionalism, Reward, and Punishment on the Performance of East Bolaang Mongondow Police Personnel partially and simultaneously. The data analysis technique in this study used multiple linear regression analysis. The results of the study show that (1) Professionalism has a significant effect on the Performance of the Bolaang Mongondow Timur Resort Police Personnel, (2) Reward has a significant effect on the Performance of the Bolaang Mongondow Timur Resort Police Personnel, (3) Punishment has a significant effect on the Performance of the Bolaang Mongondow Timur Resort Police Personnel and (4) Professionalism, Reward and Punishment simultaneously have a significant effect on the Performance of the Bolaang Mongondow Timur Resort Police Personnel.